Improving the global exchange of germplasm for crop breeding - Louafi, Selim (Burleigh Dodds Series in Agricultural Science, 2021)
Different norms, rules and practices organize the exchange of germplasm to address broader global challenges such as advancement of science and innovation, food security, sustainable agriculture or global equity. Some of these institutions are now embedded in various treaties and national regulations. This chapter claims that these regulations are not as successful as they could be because they fail to effectively integrate the complexity of the exchange environment. In order to better understand how exchange could be improved, it is important to go beyond a legalistic approach to exchange and look at the broader socio-technical context in which these exchanges take place. By developing an analytical framework that includes several dimensions beyond the regulatory one, this contribution creates the foundation for a more comprehensive approach that acts upon the relationship between germplasm and the diversity of institutional logics, germplasm and its resource system, and germplasm and its social environment.